Liquefied petroleum gas (LPG) monitoring system - ESA, NASARUDDIN (IRC, 2019)
First and foremost, I would like to convey my heartfelt appreciation to Allah S.W.T for His guidance, blessing and offering me the power to fulfil my obligation as a final year student of Universiti Teknologi PETRONAS and finish this dissertation report within the given period of time. My sincere thanks and thanks go to my supervisor, En. Faizal Bin Ahmad Fadzil supports, thoughts and relentless support throughout the semester for his ongoing guidance. I think his guidance gives me the images to decide on my future career journey. I would also like to thank my dear parents who first sowed the seeds of education in me and my family, who gave me assistance and encouragement from the start to the end of this internship throughout my education. Finally, thanks to all my mates throughout the course of finishing the program, they share their experiences and support.